Characteristics of Adolescents Affected by Mass Psychogenic Illness Outbreaks in Schools in Nepal: A Case-Control Study - Sapkota, Ram P.; Brunet, Alain; Kirmayer, Laurence J. (Frontiers in Psychiatry, 2020)
This paper presents the first systematic case-control study of correlates of mass psychogenic illness (MPI) in an adolescent school population. MPI is generally construed as a dissociative phenomenon spread by social contagion to individuals who are prone to dissociation. We sought to test if the correlates of dissociative experiences most commonly proposed in the literature could predict caseness among students affected by episodes of mass psychogenic illness occurring in schools in Nepal. We assessed 194 cases and 190 controls (N = 384) of ages 11–18 years from 12 public schools. Cases and controls were comparable on all demographic variables, except for family configuration, with nuclear families more common among those affected. In bivariate comparisons, caseness was associated with childhood physical neglect and abuse, as well as living in nuclear families, peritraumatic dissociation, dissociative tendencies, and depressive and post-traumatic stress symptoms. Hypnotizability emerged as the strongest correlate of psychogenic illness among the cognitive and personality trait variables. However, in multivariable logistic regression, the correlates of dissociation did not predict caseness, suggesting that they do not adequately account for the phenomenon of mass psychogenic illness. An ad-hoc Classification and Regression Trees analysis showed that if an adolescent was highly hypnotizable and reported high rates of peritraumatic dissociative experiences, then there was a 73% probability of being a case in a mass psychogenic illness episode. Future studies involving other psychological, social and cultural factors, as well as school- and family-related factors are needed to understand the correlates of mass psychogenic illness and guide prevention and intervention.